Differences between Australian adolescents with eating disorder symptoms who are in treatment or not in treatment for an eating disorder. Issue 4 (2nd September 2020) - Trompeter, Nora; Bussey, Kay; Forbes, Miriam K.; Mond, Jonathan; Hay, Phillipa; Basten, Christopher; Goldstein, Mandy; Thornton, Christopher; Heruc, Gabriella; Byrne, Susan; Griffiths, Scott; Lonergan, Alexandra; et al.
Abstract: Background: Mental health problems frequently occur during adolescence, however, few adolescents seek treatment for these problems, especially for eating disorders. The current study aimed to quantify how adolescents in a clinical sample (ie, those receiving treatment for an eating disorder), differ in terms of psychological factors (eating disorder symptoms and psychological distress), compared to adolescents with eating pathology in a community sample (ie, those not receiving treatment). Method: Data were used from a community sample of adolescents with eating disorder pathology who have not sought treatment (n = 1011) and a clinical sample of adolescents presenting at eating disorder services for treatment (n = 153). Participants reported demographics and completed questionnaires assessing weight/shape concerns, disordered eating and psychological distress. Results: Adolescents with a lower BMI, more frequent purging and higher weight/shape concerns were more common in the clinical sample, while those engaging in more frequent driven exercise were less common in the clinical sample. The samples did not differ in severity of psychological distress. Conclusions: The findings highlight the need for increasing mental health literacy about the role of BMI and driven exercise in eating disorder symptom presentation to increase early detection of these disorders among adolescents.